Assessment of high-resolution methods in hypersonic real-gas flows - Tissera, Shiroshana (Cranfield University, 2010)
The interest in hypersonic flow phenomena has peaked in recent years where number of experimental and computational work has been carried out. The Computational Fluid Dynamics (CFD) is fast becoming an invaluable tool to investigate compressible hypersonic flow phenomena that are extremely complex in nature. Mathematical models employed to describe complex physical phenomena that take place at hypersonic speeds inherit varying degrees of accuracy and reliability. Therefore, further studies, numerical and experimental, are needed to clarify and improve these models. Numerical computation is one of the tasks that are vital in the overall hypersonic flow research effort. This work investigated the applicability and performance of higher resolution methods to simulate high enthalpy real gas flows. Furthermore, gas-surface interaction and ablation effects are also investigated. In order to achieve the set task, it is imperative that the numerical code (CNS3D) used is equipped with necessary numerical and physical models to tackle flow behaviour typically unique to hypersonic flow. Therefore, the implementation of mathematical models that describe the real gas phenomena, such as vibrational effects, chemical dissociation, diffusion, and high enthalpy effects, has been carried out. The test cases, the HB-2 flare and the double-cone have been considered for the purposes of verification and validation. The experimental data for heat transfer and pressure are compared with numerical predictions to assess the behaviour of modified CNS3D overall and each numerical scheme with regards to reconstruction methods. The overall agreement between the predicted results for both cases and the experimental data is satisfactory. The stagnation point values of pressure and heat flux for HB-2 flare testcase at varying Mach numbers from 5 to 17.8 has been established; these values are expected aid future validation efforts. It was also found that very high-order schemes, such as WENO 5th and 9th -order methods, may provide slightly better results for free stream Mach numbers less than 10; however, there are no obvious benefits over second-order methods for Mach numbers greater than 10. Furthermore, it has been substantiated that increasing order of accuracy compared to increments in the grid resolution is much more effective way of gaining accuracy in the case of real gas flows.